Hope rises [compact disc, unabridged] - Baldacci, David (Baldacci, David. Walter Nash series., 2026)
Walter Nash, working under the alias of Dillon Hope, is on the road to revenge after becoming an informant for the FBI against a global criminal operation headed up by Victoria Steers. His only goal in life is taking down Steers. In order to succeed, he's going to need to cross enemy lines and work the job from the inside. But Steers is shrewd and only brings those she trusts completely into her inner circle. Nash must rely on every ounce of his hard-earned skills in order to prove himself an ally to Steers if he's ever going to get close enough to decimate her criminal empire.